Wrapped in stardust: glam rock and the rise of David Bowie as pop entrepreneur. Issue 4 (4th July 2017) - Bennett, Andy
Abstract: Among those artists who define 1970s glam rock, David Bowie holds a unique place. Together with a handful of other glam artists (including Roxy Music and Marc Bolan), Bowie successfully straddle the pop singles and AOR markets. Such a position enabled Bowie to explore key characteristics of glam, including its emphasis on nostalgia. Moreover, Bowie's sophisticated understanding of glam as an ephemeral assemblage of stylistic fragments also set him apart from others in the glam rock scene. Whereas many glam artists later struggled with the legacy that glam imposed on them, Bowie's ability to read it in a broader context of pop fads and fashions meant he could exploit the aesthetics of glam to his advantage. This article considers how Bowie tactically used glam to raise his profile as a pop icon while subsequently applying it as a conceptual blueprint for the performative identities he assumed later in his career.